Does Status Equal Substance? The Effects of Specialist Social Status on Auditor Assessments of Complex Estimates - Gold, Anna; Kadous, Kathryn; Leiby, Justin (The Accounting Review, 2024)
ABSTRACT Auditing standards require that auditors’ reliance on a specialist is commensurate with the specialist’s competence. In assessing competence, auditors encounter cues diagnostic of the specialist’s social status but less so of competence. In an experiment, we manipulate specialist status and find that auditors mistake status for competence unless they are prompted to separate the constructs. This raises the possibility that auditors could over-rely on high-status specialists. However, auditors also assess high-status specialists as more influential, and when the specialist disagrees with the client, they rely more on high-status specialists because of this perceived influence. Thus, high-status specialists can increase auditors’ willingness to challenge the client by providing a strong ally. Additional analyses suggest that auditors are aware that they rely on the specialist’s influence rather than competence, indicating that auditors do not use the process that auditing standards envision to evaluate and rely on specialists. Data Availability: Data are available upon request. JEL Classifications: M42.